Molekulárně genetická příčina a klinický nález u dvou probandů se Stargardtovou chorobou - Kousal, B; Záhlava, J; Vejvalková, Š; Hejtmánková, M; Lišková, P (Ceska a slovenska oftalmologie, 2014)
PURPOSE: The aim of our study was to describe the phenotype and to perform molecular genetic investigation in two probands of Czech origin diagnosed with Stargardt disease (STGD). METHODS: Both males underwent ocular examination including assessment by high-resolution spectral domain optical coherence tomography (SD-OCT). DNA was isolated from venous blood. Mutation detection was performed using the ABCA4 genotyping microarray (Asper Ophthalmics, Estonia). RESULTS: The best corrected visual acuity in proband 1 (aged 39 years) was 0.1 bilaterally, and 0.05 in proband 2 (aged 26 years). Fundus examination showed typical multiple yellow-white lesions and macular atrophy. Alterations of retinal pigment epithelium, retinal thinning and disruption of the photoreceptor inner segment ellipsoid band were detected with an SD-OCT. Two known disease-causing mutations in ABCA4 were identified in proband 1; c.4234C>T, p.(Gln1412*) in exon 28; and c.5882G>A, p.(Gly1961Glu) in exon 42. Only one pathogenic change was detected in proband 2; c.1988G>A, p.(Trp663*) in exon 14. A second change, anticipated because of the recessive status of the disease, was not identified. CONCLUSION: The frequency and full spectrum of ABCA4 mutations in Czech patients with inherited retinal disorders is yet to be established. The inability to detect a second pathogenic change in ABCA4 coding sequences in proband 2 warrants further investigation.
Keywords: optická koherentní tomografie; Fundus Oculi; DNA Mutational Analysis; Male; zraková ostrost; mutace; Electroretinography; Genotype; Macular Degeneration; zevní segment tyčinky; Fluorescein Angiography; Adult; dospělí; mužské pohlaví; Visual Acuity; mutační analýza DNA; Rod Cell Outer Segment; lidé; ženské pohlaví; Humans; Stargardtova nemoc; fundus oculi; makulární degenerace; Tomography, Optical Coherence; DNA; fluoresceinová angiografie; genotyp; ABC transportéry; Mutation; elektroretinografie; Female; Stargardt Disease; ATP-Binding Cassette Transporters